DABCO: An Efficient Catalyst for Pseudo Multi-component Reaction of Cyclic Ketone, Aldehyde and Malononitrile - M. Chinchkar, Sarika; D. Patil, Jayavant; N. Korade, Suyog; S. Gokavi, Gavisiddappa; V. Shejawal, Rajendra; M. Pore, Dattaprasad (Letters in Organic Chemistry, 2017)
Background: Designing efficient methods for the synthesis of complex molecules with predefined functionalities is a challenging task in modern organic chemistry. In this context, multicomponent reactions (MCRs), by virtue of their applications, constitute a central academic and industrial investigation domain. Recently, MCRs involving vinylogous Michael addition have attracted increasing interest as one of the most useful key reactions for the synthesis of poly substituted benzene derivatives such as spiro[cyclohexanes-1,3'-indoline]-2';,3-diones, spiroacenaphthylene, benzo[α]cyclooctenes, etc. Therefore, development of an efficient method for a MCR which encompass vinylogous Michael addition as vital reaction is of current interest. Methods: We explored catalytic efficiency of DABCO in the multi-component reaction of cyclic ketone, aldehyde and two moles of malononitrile for the synthesis of functionalized condensed bicyclic compounds viz tetrahydroindenes, tetrahydronaphthalenes, hexahydrobenzo[7] annulenes and hexahydrobenzo[ 8]annulenes. Results: The reaction conditions were optimized by screening of catalyst and solvent. Employing optimized reaction conditions library of bicyclic compounds viz. tetrahydroindenes, tetrahydronaphthalenes, hexahydrobenzo[7]annulenes and hexahydrobenzo[8]annulenes were synthesized in short time duration. The synthesized products were characterized by 1H, 13C, IR and MS. Spectral data obtained was in good agreement with the structure of products. Conclusion: We disclosed DABCO catalyzed multi-component reaction of aldehyde, cyclic ketone and malononitrile furnished corresponding tetrahydronaphthalenes, tetrahydroindalenes, hexahydrobenzo[7] annulenes and hexahydrobenzo[8]annulenes, with a high level of complexity. Notably, this methodology provides a facile access to various multi-functional compounds. The operational simplicity and good yields, combined with step and atom-economic aspects, clean reactions yielded pure products, hence no requirement of tedious chromatographic purification makes this synthetic strategy highly attractive and promising approach from sustainable and practical chemistry.
Keywords: multi-component